The reliability, validity and trainability of running economy in trained distance runners - Shaw, A. J. (2016)
Running economy is well established as a primary determinant of endurance running performance. However, there is a lack of clarity about the preferred measurement of running economy, its primary limiting factors and the most robust methods enhance running economy in highly trained athletes. Therefore, this thesis investigated the running economy of highly trained runners, exploring the reliability and validity of measures of running economy to deduce its most appropriate quantification, the application of innovative methods to enhance our understanding of an athlete s running economy, and a novel training method to enhance running economy. Chapter 3 revealed that energy cost and oxygen cost were shown to provide similarly high levels of reliability (typical error of measurement ~3%) for highly trained endurance runners when assessed using a short-duration incremental submaximal exercise protocol. In chapter 4, the analysis of a large cohort of highly trained endurance runners revealed that energy cost increased in a stepwise manner with increments in running speed (P<0.001), however oxygen cost remained consistent (P=0.54) across running speed; indicating that oxygen cost might not be an appropriate measure of running economy. Chapter 5 demonstrated that the inter-individual variation in the magnitude of changes in energy cost between different gradients (i.e. from flat running to uphill/downhill running) in highly trained runners was low. However, a disparity between the energy saving of running on a -5% gradient (-17%) and the additional energy cost of running on a +5% gradient (+32%) was evident. The cross-sectional and longitudinal analysis of a large cohort of highly trained runners in chapter 6 revealed a small (r=0.25) and moderate (r=0.35) association between energy cost and maximal oxygen uptake, respectively. Finally, chapter 7 demonstrated that eight weeks of supplementary downhill run training at vLTP in existing training programmes does not enhance running economy in already well trained runners (1.22 vs 1.20 kcal kg-1 km-1; P=0.41), despite a significant increase (+2.4%) in the velocity at lactate turnpoint. In conclusion, this thesis demonstrates that energy cost, expressed as kcal kg-1 km-1, provides a reliable and valid method to quantify running economy in trained distance runners. However, further investigation is required to identify robust training methods to enhance running economy in this already highly trained population.